Functions of boundary spanning in context: A postcolonial, power-sensitive perspective - Isabel Collien (Helmut-Schmidt-Universität, Forschungscluster OPAL, 2019)
Functions of boundary spanning have seldom been the focal point in boundary spanning research. This is surprising given the close entanglement of interests and power (relations), and the early emergence of power-sensitive boundary spanning studies. This paper traces the influence of macro-level, race-related power relations on functions of boundary spanning, using the example of a German public administration. The findings show that power relations influence why and how actors engage in boundary spanning across levels of analysis. A counter-hegemonic reading of the results shows that the particular functions of boundary spanning resemble colonial patterns of mediating between the colonizer and the colonized.
Keywords: 300; boundary spanning; interests; culture; identity; postcolonial; power